Musykilat Ta’lim Al-Lughah Arabiyah Fii Madrasah Tarbiyah ‎Islamiyah Bayur Agam - Quratul Aini (Universitas Islam Negeri Imam bonjol Padang, 2023)
This research problem is the problem of learning Arabic at MTI Bayur. ‎Arabic language learning is divided into two parts: linguistic and non-linguistic. ‎The problem of teaching Arabic that the author refers to is a non-linguistic ‎problem that must be solved. Non-linguistic problems found in MTI Bayur are ‎teacher competence, textbooks and infrastructure. So this article reveals the ‎learning problems that exist in MTI Bayur. The formulation of the problem in ‎this study is